The Problem of Being Someone - Priest, Stephen (Eidos. A Journal for Philosophy of Culture, 2024)
There is a genuine and profound problem about what it consists in for anything to be yourself. Once (perhaps per impossibile) all the empirical and modal facts about a particular human being are in, it still remains unexplained both what being you is, and why that human being is yourself. Being you seems an “extra” feature of anything. The problem admits of no scientific solution, and “being you” resists any purely logical analysis. It is argued that the problem is metaphysical, and that because metaphysical problems have theological answers, being you, and why anything is you may only be explained theologically. You are this soul, this immaterial presence, created by God. A new argument for the existence of God, the Autological Argument, is briefly presented.